The forest of information: beating paths through the jungle - Paivinen, R.; Mills, R.; Hailu, M.; Saarikko, J. (2001)
In this article an outline is given of the history of information and publishing in forestry, communications technology is described (including mobile computing, GIS and satellite observations), and the future exchange of information via the Internet and web-based services is discussed. Two examples show the use of computer technology and decision support systems to prepare a forest management plan and to purchase a hardwood table for the garden. A section is included on The Global Forest Information Service (GFIS), being developed by IUFRO, which is based on a distributed network of metadatabases which catalogue the information resources (digitalized or not) of contributing partners.